MALDI mass spectrometry imaging: From constituents in fresh food to ingredients, contaminants and additives in processed food. (15th August 2022) - Kokesch-Himmelreich, Julia; Wittek, Oliver; Race, Alan M.; Rakete, Sophie; Schlicht, Claus; Busch, Ulrich; Römpp, Andreas
Highlights: Investigation of fresh and processed food by MALDI mass spectrometry imaging. Visualization of different compound classes in plant and meat-based food. Development of data processing tool for penetration/diffusion analysis (in food). Natamycin penetration in cheese, first visualization of food additive by MS imaging. Acrylamide in gingerbread, first visualization of contaminant in processed food by MS imaging. Abstract: Mass Spectrometry imaging (MS imaging) provides spatial information for a wide range of compound classes in different sample matrices. We used MS imaging to investigate the distribution of components in fresh and processed food, including meat, dairy and bakery products. The MS imaging workflow was optimized to cater to the specific properties and challenges of the individual samples. We successfully detected highly nonpolar and polar constituents such as beta-carotene and anthocyanins, respectively. For the first time, the distributions of a contaminant and a food additive were visualized in processed food. We detected acrylamide in German gingerbread and investigated the penetration of the preservative natamycin into cheese. For this purpose, a new data analysis tool was developed to study the penetration of analytes from uneven surfaces. Our results show that MS imaging has great potential in food analysis to provide relevant information about components' distributions, particularly those underlying official regulations.